ANALYSIS OF TOMATO FARMING IN KATENZO FARMER GROUPS, PANGALENGAN, WEST JAVA - Pardian, Pandi (Jurnal Ilmiah Mahasiswa AGROINFO GALUH, 2024)
The Katenzo farmer group is one of the vegetable producers in Pangalengan District, which cultivates tomatoes and is a partner for fertilizer producers in making demonstration plots. This research aims to determine the cost analysis in tomato farming in the Katenzo Farming Group. The research calculates a 1-hectare land area from the average member land area as 100 tumbak or 1,400 square meters or 0.14 ha. The results show that tomato farming in the Katenzo Farming Group with a land area of 1 (one) hectare produces an R/C ratio of 2.03 with a production yield of 57,143 kg, more significant than the BEP (production volume) of 12,540 kg and also an income of Rp. 101,623,214,- greater than the BEP (rupiah) of Rp. 43,890,329,- shows that tomato farming in the Katenzo Farming Group is feasible and profitable to develop.